The Problem of Literary and Journalistic Mastery in Uzbek Literary (Eurasian Journal of Media and Communications, 2022)
The present article covers creativity and analytical skills of one of the brightest representatives of Uzbek literal studies and critics Matyoqub Qo'shjonov. A writer separately studies issues of character, plot, composition and conflict in his works. Main genres of M.Qo'shjonov - review, articles, supervisions, interviews, sketches, essays, previews, letters, monographs among which a main place is given to articles, sketches and essays.